Empagliflozin for liver and lipid profile in metabolic dysfunction-associated fatty liver disease: a meta-analysis - Suhardi, Kevin Fernando; Sutadji, Jonathan Christianto; Putri, Agustina Rajendra; Tsamara, Ghina; Faratisha, Icha Farihah Deniyati; Viazelda, Aqsha Tiara; Soeslistijo, Soebagijo Adi (Faculty of Medicine Universitas Indonesia, 2025)
BACKGROUND Metabolic dysfunction-associated fatty liver disease (MAFLD) is a common chronic liver condition often associated with obesity and diabetes. Empagliflozin, a sodium-glucose cotransporter 2 inhibitor, is an antidiabetic medication that improves glycemic control, insulin resistance, and body weight. This study aimed to examine the efficacy of empagliflozin in adults with MAFLD. METHODS A comprehensive literature search was performed using the PubMed, ScienceDirect, Cochrane Library, Scopus, and Wiley Online Library databases. Randomized controlled trials assessing liver function, lipid profile, metabolic profile, and body composition were included. Weighted mean differences (WMDs) and 95% confidence intervals (CIs) were calculated using random-effects models, and study quality was assessed using the Cochrane Risk of Bias Tool for Randomized Trials. RESULTS 6 RCTs with a total of 636 participants were analyzed. Empagliflozin significantly reduced alanine aminotransferase levels (WMD: –6.65 IU/l, 95% CI: –13.02 to –0.28; p = 0.04) and gamma-glutamyl transferase levels (WMD: −10.60 IU/l, 95% CI: −29.05 to −7.68; p<0.00001). A non-significant reduction in aspartate aminotransferase was observed (WMD: –4.69 IU/l, 95% CI: –9.89 to 0.51; p = 0.08). Empagliflozin significantly improved low-density lipoprotein cholesterol (p = 0.02) and total cholesterol (p = 0.05) levels but did not significantly affect triglycerides, high-density lipoprotein cholesterol, metabolic profiles, or body composition. CONCLUSIONS This meta-analysis highlights the beneficial effects of empagliflozin on liver function and indicates the need for further research on its metabolic effects and long-term outcomes in managing MAFLD.